2015
DOI: 10.1371/journal.pone.0135655
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Co-Occurrence of ExoR, ExoS, and ChvI, Components of the RSI Bacterial Invasion Switch, Suggests a Key Adaptive Mechanism Regulating the Transition between Free-Living and Host-Invading Phases in Rhizobiales

Abstract: Both bacterial symbionts and pathogens rely on their host-sensing mechanisms to activate the biosynthetic pathways necessary for their invasion into host cells. The Gram-negative bacterium Sinorhizobium meliloti relies on its RSI (ExoR-ExoS-ChvI) Invasion Switch to turn on the production of succinoglycan, an exopolysaccharide required for its host invasion. Recent whole-genome sequencing efforts have uncovered putative components of RSI-like invasion switches in many other symbiotic and pathogenic bacteria. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 101 publications
(164 reference statements)
1
24
0
Order By: Relevance
“…The proliferation of studies investigating Bartonella in various wildlife populations allows for greater insights into the origins and evolution of Bartonella and its potential for spillover more than ever before. Bartonellaceae is nested within the Rhizobiales, a lineage of soil bacteria that contains nitrogen-fixing root-associated members (13). In our study, B. apis was the most basal strain of Bartonella .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferation of studies investigating Bartonella in various wildlife populations allows for greater insights into the origins and evolution of Bartonella and its potential for spillover more than ever before. Bartonellaceae is nested within the Rhizobiales, a lineage of soil bacteria that contains nitrogen-fixing root-associated members (13). In our study, B. apis was the most basal strain of Bartonella .…”
Section: Discussionmentioning
confidence: 99%
“…The 16s rRNA gene is much less powerful for discriminating Bartonella species than gltA (7) and often metagenomic studies amplify only very small fragments of the gene, making it difficult for us to resolve fine scale diversification but we were able to determine that basal strains of Bartonella were largely found in environmental samples and non-hematophagous insects (Figure 1). Additionally, work on Bartonella has shown that the evolution of a type 4 secretion system, along with selection on other invasion mechanisms (13), has been instrumental in allowing Bartonella to diversify and invade host cells (23, 24) while other work has shown Bartonella can incorporate a type 4 secretion system via lateral gene transfer when it coinfects an amoeba with Rhizobium radiobacter (25). Further, examinations of lateral gene transfer of metabolic genes in Bartonella reveals that many of these genes derive from common insect gut commensal bacteria (26).…”
Section: Discussionmentioning
confidence: 99%
“…ExoS is a membrane-bound histidine kinase with a periplasmic sensing domain and ChvI is a response regulator of the OmpR/PhoB family of response regulators (Cheng and Walker, 1998). ExoS/ChvI has orthologs in related α-proteobacteria (Vanderlinde and Yost, 2012;Heavner et al, 2015), and orthologs such as BvrS/BvrR in the mammalian pathogen Brucella abortus and ChvG/ChvI in the plant pathogen Agrobacterium tumefaciens are required for virulence (Charles and Nester, 1993;Sola-Landa et al, 1998;Heavner et al, 2015). ChvG/ChvI-dependent transcription is activated by acidic pH and BvrS/BvrR-dependent transcription is activated by acidic pH and nutrient limitation (Yuan et al, 2008;Altamirano-Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of studies investigating Bartonella in various wildlife populations allows for greater insights into the origins and evolution of Bartonella and its potential for spillover more than ever before. Bartonellaceae is nested within the Rhizobiales, a lineage of soil bacteria that contains nitrogen-fixing root-associated members [ 43 ]. In our study, the most basal strains of Bartonella were found in environmental samples and arthropods (Figs 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 16s rRNA gene is much less powerful for discriminating Bartonella species than gltA [ 7 ] and often metagenomic studies amplify only very small fragments of the gene, making it difficult for us to resolve fine scale diversification but we were able to determine that basal strains of Bartonella were largely found in environmental samples and non-hematophagous insects ( Fig 1 ). Additionally, work on Bartonella has shown that the evolution of a type 4 secretion system, along with selection on other invasion mechanisms [ 43 ], has been instrumental in allowing Bartonella to diversify and invade host cells [ 46 , 47 ] while other work has shown Bartonella can incorporate a type 4 secretion system via lateral gene transfer when it coinfects an amoeba with Rhizobium radiobacter [ 48 ]. Further, examinations of lateral gene transfer of metabolic genes in Bartonella reveals that many of these genes derive from common insect gut commensal bacteria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%